Adaptive Routing using Relative Cost Concept in Elastic Optical Networks with Space-Division Multiplexing - Alyatama, Anwer; Ali, Mona (Journal of Applied Informatics and Technology, 2025)
Elastic Optical Networks with Space Division Multiplexing Networks (EON-SDM) is the most prominent technology for efficiently transmitting massive amounts of data flow and dealing with the explosion of new technologies that require a wide range of services. Among the various factors that determine network efficiency, performance, and design effectiveness in EON-SDM networks is routing, spectrum, and core allocation (RSCA). RSCA’s strategic optimization ensures efficient data transmission, effortlessly meeting the demands of high-bandwidth applications. Within this study, we propose a relative cost-based adaptive RSCA algorithm that prioritize long-term state consequences in accepting new calls. When a call is received, the proposed approach picks the route, core, and spectrum group with the lowest relative cost and compares it to the call’s value, in the event that the minimum computed relative cost of the arrival call is greater than the call value, the call is blocked. Comparative analysis with established routing methods reveals promising performance outcomes, including a 45% reduction in normalized loss revenue and a 155% enhancement in fairness in certain scenarios.